319. Presepsin as a Prognostic Biomarker for Mortality in COVID-19 Patients vs Community-Adquired Pneumonia (CAP) Patients. (4th December 2021) - Morales-Cely, Lina; Bravo-Castelo, Laura A; Bustos-Moya, Ingrid G; Fuentes, Yuli; Lozada-Arciniegas, Julian; Ibañez-Prada, Elsa Daniela; Narváez - Ramírez, Oriana; Ramirez, Paula; Parra-Tanoux, Daniela; Gomez-Duque, Salome; Gamboa-Silva, Enrique; Caceres, Eder; et al.
Abstract: Background: Lower respiratory tract infections such as community-acquired pneumonia (CAP) and coronavirus disease 2019 (COVID-19) are the main current causes of mortality worldwide. Several scores and biomarkers have been proposed to identify patients at risk of dying, with unclear results. Presepsin is a glycoprotein expressed on the surface of the membrane of monocytes and macrophages and its utility has been proven in sepsis as a predictor of severity and treatment response. However, it is unknown the utility of this biomarker as a mortality predictor among COVID-19 and CAP patients. Thus, the aim of this study was to determine the utility of serum presepsin to identify patients at risk of dying due to COVID-19 and CAP. Methods: A prospective observational study was conducted at Clinica Universidad de La Sabana, Colombia. We included 240 patients who required hospital admission due to CAP or COVID-19. Plasma samples were collected within 24 hours of admission. The presepsin concentration was quantified using the PATHFAST system. Afterwards, a two-tailed test was used to compare mortality rates among patients and their presepsin plasma concentration. Lastly, the ROC was calculated to determine presepsin's sensibility as a mortality predictor. Results: A total of 88 patients with CAP and 152 patients with COVID-19 were included in the study. The median [with IQR] in Presepsin plasma concentration was higher in all patients who died (920 [573 - 2340] vs 573 [307, 5 - 1052, 5], p-value< 0.0001 ). Furthermore, comparing to the study group, the median concentration of presepsin was higher in patients deceased by COVID-19 than those who survived. (1358 [642, 8 - 2976, 8] vs 570 [333, 2 - 1007, 5], p-value< 0.0001 ). In addition, the area under the curve (AUC) ROC of presepsin to predict risk of mortality was 0.769. DeLong's test comparing ROC curves in COVID-19 and CAP patients had a p-value=0.073 . Serum presepsin results Conclusion: Plasma concentrations of presepsin plasma were higher among COVID-19 patients who died. Moreover, serum concentration of presepsin were not useful to identify CAP patients at risk of dying. However, practical use of Presepsin as a prognostic biomarker of severity is yet to be assessed as further studies are needed. Disclosures: All Authors : No reported disclosures